Between Profit and Planet: A Critical Examination of Sustainability Practices in Indonesia’s Muslim Fashion Industry - Nugroho, Leonyta (INDEF - Institute for Development of Economics and Finance, 2025)
In response to the climate crisis, the fashion industry remains a significant contributor to global carbon emissions. This study explores how Islamic ethical principles can inform sustainable business practices in Indonesia's modest fashion sector, which serves the world's largest market of Muslim-majority consumers. Employing quantitative carbon footprint assessments of six Muslim fashion brands across different enterprise scales. Data were collected from Instagram–to categorize brands based on market size–and Shopee, providing product-specific information on materials and sales volumes. Emissions were calculated following the Greenhouse Gas Protocol (2004), using DEFRAâ€™s standardized emission factors for apparel. The result reveals variability in emissions among brands, highlighting the importance of material choices and transparency. To address these challenges, this study introduces the HIFZH-Model, a faith-inspired sustainability model, along with a 20-point checklist for aligning business practices with Islamic environmental values. This research offers a culturally relevant model for fostering low-carbon entrepreneurship within Muslim communities.